KEPUASAN PELANGGAN SEBAGAI MEDIASI PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN (Studi Pada J&T Express Kota Malang) - ALDI WIRADWIPA PRASETYA ; Dr. Astrid Puspaningrum, SE., MM (Manajemen FEB - UB, 2018)
This study aims to determine the effect of service quality on customer loyalty on the J&T Express Malang directly and indirectly through customer satisfaction. This type of research is explanatory research with a quantitative approach through questionnaire method which is distributed offline. The population of this study is the consumer of J&T Express Malang who had made transactions or purchased in J&T Express with a minimum of 2 times usage, has aged ? 17 years and for whom is the decision maker. The sample in this research is 100 respondents by using purposive sampling technique. Data analysis using Structural Equation Modeling (SEM) with SmartPLS 3.0 software (Partial Least Square). From the results of this study found that service quality has a significant and positive effect on customer loyalty directly and indirectly through customer satisfaction. Keywords: Service quality, Customer loyalty, Customer satisfaction